Homogeneous nucleation rate measurements of 1-propanol in helium: the effect of carrier gas pressure - Brus, David; Zdímal, Vladimír; Stratmann, Frank (The Journal of chemical physics, 2006)
Kinetics of homogeneous nucleation in supersaturated vapor of 1-propanol was studied using an upward thermal diffusion cloud chamber. Helium was used as a noncondensable carrier gas and the influence of its pressure on observed nucleation rates was investigated. The isothermal nucleation rates were determined by a photographic method that is independent on any nucleation theory. In this method, the trajectories of growing droplets are recorded using a charge coupled device camera and the distribution of local nucleation rates is determined by image analysis. The nucleation rate measurements of 1-propanol were carried out at four isotherms 260, 270, 280, and 290 K. In addition, the pressure dependence was investigated on the isotherms 290 K (50, 120, and 180 kPa) and 280 K (50 and 120 kPa). The isotherm 270 K was measured at 25 kPa and the isotherm 260 K at 20 kPa. The experiments confirm the earlier observations from several thermal diffusion chamber investigations that the homogeneous nucleation rate of 1-propanol tends to increase with decreasing total pressure in the chamber. In order to reduce the possibility that the observed phenomenon is an experimental artifact, connected with the generally used one-dimensional description of transfer processes in the chamber, a recently developed two-dimensional model of coupled heat, mass, and momentum transfer inside the chamber was used and results of both models were compared. It can be concluded that the implementation of the two-dimensional model does not explain the observed effect. Furthermore the obtained results were compared both to the predictions of the classical theory and to the results of other investigators using different experimental devices. Plotting the experimental data on the so-called Hale plot shows that our data seem to be consistent both internally and also with the data of others. Using the nucleation theorem the critical cluster sizes were obtained from the slopes of the individual isotherms and compared with the Kelvin prediction. The influence of total pressure on the observed isothermal nucleation rate was studied in another experiment, where not only temperature but also supersaturation was kept constant as the total pressure was changed. It was shown that the dependence of the nucleation rate on pressure gets stronger as pressure decreases.